LEARNING FROM ARCHITECTURE OF METABOLISM: FUTURE CITY AND URBANISM - Eken, Cemaliye (Open House Int, 2017)
Rapid urbanization and providing pragmatic solutions for its development is one of the fundamental agenda of last decade. The metabolism is one of the latest post-war movements-founded in 1960 by Kenzo Tange where urbanization and city as a process is re-examined within the framework of accelerated modernism and technology vision. This paper discusses Metabolism movement in order to identify crucial intimations of its utopian architectural and urban approaches as a tool for future city. The study examines four initial metabolist city approaches-Plan for Tokyo (1960-62), Clusters/city in the Air (1960-62), Helix city (1961) and Ocean/Marine City (1962) that are designed for post-war Tokyo city in Japan. The study gives modest insight of indentifying city design theory within in a series conception; such as conducting to architectural characteristics regarding urban structure, tectonic vision between land-seasky and organic notion (city as process and mega-structuralism). Research method is embodied with examining relevant data of literature data. Upon discussions on theory, study aims to establish an ironic notion of future city by asserting familiar characteristics or variations between four pioneer projects of Metabolist movement.
Keywords: Urban Growth; Urban Development; Future City; Sustainability; Metabolism